Antibacterial Efficacy of Iron-Oxide Nanoparticles against Biofilms on Different Biomaterial Surfaces - Thukkaram, Monica; Sitaram, Soundarya; Kannaiyan, Sathish kumar; Subbiahdoss, Guruprakash (International Journal of Biomaterials, 2014)
Biofilm growth on the implant surface is the number one cause of the failure of the implants. Biofilms on implant surfaces are hard to eliminate by antibiotics due to the protection offered by the exopolymeric substances that embed the organisms in a matrix, impenetrable for most antibiotics and immune cells. Application of metals in nanoscale is considered to resolve biofilm formation. Here we studied the effect of iron-oxide nanoparticles over biofilm formation on different biomaterial surfaces and pluronic coated surfaces. Bacterial adhesion for 30 min showed significant reduction in bacterial adhesion on pluronic coated surfaces compared to other surfaces. Subsequently, bacteria were allowed to grow for 24 h in the presence of different concentrations of iron-oxide nanoparticles. A significant reduction in biofilm growth was observed in the presence of the highest concentration of iron-oxide nanoparticles on pluronic coated surfaces compared to other surfaces. Therefore, combination of polymer brush coating and iron-oxide nanoparticles could show a significant reduction in biofilm formation.